ANALISIS PERKEMBANGAN SOSIAL ANAK TUNARUNGU USIA 4-5 TAHUN TK ALIFA KIDS 6 PEKANBARU - Putri Clawson; Sherly Damayanti (P3M STKIP 'Aisyiyah Riau, 2020)
This study aims to obtain data on the social development of deaf children aged 4-5 years in interacting with others and their ability to communicate in the Alifa Kids 6 Kindergarten Pekanbaru school environment. In the social environment, verbal communication is the most common form of communication. Whereas in the case of deaf children, verbal communication is something that is difficult. In other words, a child's hearing loss as a result of hearing impairment, becomes hampered by the potential for developing language / speech skills. This research uses descriptive qualitative research, based on the results of the study showing that deaf children Social contact and communication of deaf children with normal children will affect the child's development. Normal children will learn to accept the shortcomings of friends and deaf children will learn how to adjust and foster self-confidence to be friends with normal friends. Barriers experienced by children with hearing impairment in addition to hearing impairments, they also have obstacles in speaking and also difficult to control this emotion which actually often inhibits children's social development. In addition, social contact and communication of deaf children with normal children will affect the child's development. Normal children will learn to accept the deficiencies that are owned by their friends and deaf children will learn to align themselves with the surrounding environment.